From gold to debt: comparative lessons from the Spanish Price Revolution and the U.S. post-2008 monetary policy - Bani Issa, Mohammad Saleh; Bani Salameh, Mohammed Torki (Frontiers in Political Science, 2025)
This paper conducts a comparative analysis of the Spanish Price Revolution (1500–1650) and the United States' post-2008 monetary trajectory to examine how sustained monetary expansion, when decoupled from real productivity growth, can generate long-term structural vulnerabilities. Drawing on the Quantity Theory of Money (QTM), Keynesian and Post-Keynesian critiques, and the political economy of imperial overstretch, the study explores how both imperial Spain and the modern United States relied on externally sourced or artificially generated wealth—colonial bullion and quantitative easing, respectively—while neglecting the renewal of domestic productive capacity. In both cases, monetary abundance contributed to inflationary pressures, deindustrialization, rising inequality, and mounting debt burdens. Although institutional differences are significant—most notably the reserve currency status of the U.S. dollar and the existence of an advanced financial infrastructure—this research argues that such advantages may only delay rather than prevent systemic fragility. By integrating historical evidence, economic theory, and geopolitical analysis, the paper demonstrates that monetary abundance cannot substitute for structural strength. The findings issue a cautionary note on the sustainability of U.S. hegemony and highlight the urgent need for reforms aimed at industrial renewal, fiscal discipline, and mitigating inequality. In doing so, the study revives classical debates in monetary economics while offering historically grounded insights for contemporary fiscal governance.